Uma leitura da Ética I de Spinoza com vistas ao método geométrico - Abrantes, Jorge Gonçalves de (2017)
Let us examine and discuss the nature and content of the principles of the first part of Spinoza's Ethics in relation to the Elements of Euclid, whose main purpose is to point out that the Spinozian principles are distinct and divergent from Euclidean principles in some respects. In this sense, we propose to point out the differences and similarities that may exist between the Euclidean geometric method and the Spinozian geometric method, in order to problematize the question of the presence of the geometric method in Spinoza ethics.